Pembuatan telur tinggi kalium menggunakan metode dan jenis telur yang berbeda - Ibnu Hufail; Nana Sutisna Achyadi; Supli Effendi (University of Insan Cendekia Mandiri, 2024)
The purpose of this research was to determine the characteristics of high potassium eggs based on different methods and types of eggs. The design that used in this research was a Randomized Block Design (RBD) with a factorial pattern on 2×3 with four replication. The experimental design was carried out in one stage, making high potassium eggs based on using different methodes and types of eggs. The different methodes were varied into dressing method (a1) and immersion method (a2). The types of eggs were varied into purebred chicken eggs (b1), duck eggs (b2), and native chicken eggs (b3). The high potassium eggs were analyzed for potassium content, water content, and organoleptic tests for taste and texture. The results of statistical analysis showed that the manufacturing method factor has a significant effect on the high potassium texture. The type of egg factor has a significant effect on water content, potassium content, and organoleptic effects on taste and texture. The interaction between two of then has no real effect. The characteristics of high potassium eggs b1 (purebred chicken eggs): potassium content 0.0191 mg and water content 31.5731%, The characteristics of high potassium eggs b2 (duck eggs) is potassium content 0.0241 mg and water content 37.0951%. The characteristics of high potassium eggs b3 (native chicken eggs) is potassium content 0.0191 mg and water content 34.1851%. The selected sample a2 (the immersion method) with b2 (the duck egg). The characteristics of high potassium eggs a2b2 is potassium content 0.0241 mg, water content 37.0951%, taste 2.8331 (somewhat dislike) and texture 3.871 (somewhat like).